AN ANALYSIS OF STUDENTS’ PROBLEMS IN SPEAKING ENGLISH - Leony - Agnesia Purba; Aunurrahman - Aunurrahman; Dian - Shinta Sari; Rahayu - Meliasari (IKIP PGRI Pontianak, 2023)
This research aimed to determine whether students experience problems in speaking English in language problems and psychological problems aspects, to find out the causes of problems in speaking English and how students overcome their problems in speaking English at SMAN 1 Semparuk. This research used a descriptive qualitative approach. The techniques of collecting data were direct communication techniques and indirect communication techniques. The data collection was collected with open-ended questionnaires and Interviews guidline. The subjects of this study were students of grade XI IPS III SMAN 1 Semparuk for the academic year 2022/2023 where the number of students amounted to 32 people. An open-ended questionnaire was distributed to 32 students, meanwhile semi-structured interviews were conducted with 7 students to corroborate data. To analyze the data, the researcher used thematic analysis. The research findings showed that the students had difficulty in speaking English, especially in pronunciation, vocabulary, and were nervous when speaking in front of the class. The causes of these difficulties are that they are afraid of being laughed at by friends, lack confidence, often use their mother tongue or local language, and limited vocabulary. They have great motivations to learn English such as wanting to go abroad with various interests, which can encourage students to overcome this problem. Students also tend to be active in their participation when they feel supported by the teacher's efforts to create a pleasant learning atmosphere such as interaction using quizzes or questions and answers. In overcoming the difficulty of speaking English students take the initiative to ask the teacher, utilize the English dictionary to follow the course, and provide responses such as learning strategy efforts with the use of image media, the teacher needs to support these students' efforts by providing appropriate direction and guidance. Keywords: Descriptive Study, Students’ Problem, Speaking English.